A mesoporous polydopamine-derived nanomedicine for targeted and synergistic treatment of inflammatory bowel disease by pH-Responsive drug release and ROS scavenging. (April 2023) - Guan, Haidi; Xu, Zhongwei; Du, Guangsheng; Liu, Qinghua; Tan, Qianshan; Chen, Yihui; Chen, Shuaishuai; Wu, Jingfeng; Wang, Fengchao; Zhang, Jixi; Sun, Lihua; Xiao, Weidong
Abstract: Repurposing clinically approved drugs to construct novel nanomedicines is currently a very attractive therapeutic approach. Selective enrichment of anti-inflammatory drugs and reactive oxygen species (ROS) scavenging at the region of inflammation by stimuli-responsive oral nanomedicine is an effective strategy for the treatment of inflammatory bowel disease (IBD). This study reports a novel nanomedicine, which is based on the excellent drug loading and free radical scavenging ability of mesoporous polydopamine nanoparticles (MPDA NPs). By initiating polyacrylic acid（PAA）polymerization on its surface, a "core-shell" structure nano-carrier with pH response is constructed. Then, under alkaline conditions, using the π-π stacking and hydrophobic interaction between the anti-inflammatory drug sulfasalazine (SAP) and MPDA, the nanomedicines (PAA@MPDA-SAP NPs) loaded efficiently (928 μ g mg −1 ) of SAP was successfully formed. Our results reveal that PAA@MPDA-SAP NPs can pass through the upper digestive tract smoothly and finally accumulate in the inflamed colon. Through the synergistic effect of anti-inflammation and antioxidation, it can effectively reduce the expression of pro-inflammatory factors and enhance the intestinal mucosal barrier, and finally significantly alleviate the symptoms of colitis in mice. Furthermore, we confirmed that PAA@MPDA-SAP NPs have good biocompatibility and anti-inflammatory repair ability under inflammation induction through human colonic organoids. In summary, this work provides a theoretical basis for the development of nanomedicines for IBD therapy. Graphical abstract: Image 1 Highlights: New oral Nanomedicine for inflammatory bowel disease (IBD) therapy based on mesoporous polydopamine nanoparticles (MPDA). PAA@MPDA-SAP has synergistic anti-inflammatory and anti-oxidative effects. PAA@MPDA-SAP has good biocompatibility and is non-toxic to human colon organoids. PAA@MPDA-SAP can effectively promote mucosal repair and has a good therapeutic effect for IBD.